National Goals of Environmental Development until 2036 - R. N. Shpakova (Мир новой экономики)
The article analyzes the targets and tasks set by the President of the Russian Federation in May 2024 within the framework of the national goal “Environmental well-being”. It has been established that these targets and tasks fully meet the need to solve the prevailing environmental problems fixed in strategic documents of a conceptual, doctrinal and strategic nature. The fact of the planned extension of measures to radically reduce harmful emissions into the atmosphere to all cities with high and very high levels of air pollution has been recognized as extremely positive. The provisions requiring clarification and detail in the development of specialized federal projects are noted. It is proposed to pay attention to the increase in the planned indicators of reforestation, taking into account the observed increase in the number and volume of forest fires in a changing climate. It is also considered advisable to supplement environmental protection projects with measures to restore degraded land in accordance with the provisions of the Environmental Safety Strategy of the Russian Federation.